Tenofovir disoproxil fumarate significantly decreases serum lipoprotein levels compared with entecavir nucleos(t)ide analogue therapy in chronic hepatitis B carriers. Issue 6 (13th July 2017) - Shaheen, A. A.; AlMattooq, M.; Yazdanfar, S.; Burak, K. W.; Swain, M. G.; Congly, S. E.; Borman, M. A.; Lee, S. S.; Myers, R. P.; Coffin, C. S.
Summary: Background: Tenofovir disoproxil fumarate (TDF) and entecavir (ETV) are first‐line treatments for chronic hepatitis B (CHB). Studies suggest lipid lowering effect of TDF in human immunodeficiency virus positive (HIV+) individuals, but the effect on lipids and cardiovascular disease (CVD) risk in CHB is unknown. Aim: To compare TDF vs ETV effects on lipid levels in CHB. Methods: In this retrospective cohort study, data on serum lipids and CVD risk factors at baseline and 1 year on TDF or ETV were collected from CHB carriers. We used propensity score matched models to assess the effect on total cholesterol (TC), LDL‐C, HDL and triglycerides (TGL). Results: In 348 patients, median age was 57 (IQR: 47‐65 years), 63% were male, 77% were Asian, 19% were cirrhotic, 25% were HBeAg positive at baseline, and 72% received TDF vs 28% ETV. ETV‐treated patients were older (median age: 60 vs 55, P <.01), had similar smoking and hypertension rates, but diabetes and dyslipidemia were more prevalent (19% vs 9%, P =.01; 14% vs 6%, P =.05, respectively). In propensity score matched models for age, gender, usage of lipid lowering agents, dyslipidemia and diabetes, TDF‐treated patients were more likely to show a 20% decrease in TC (95% CI: 3%‐25%), LDL‐C (95% CI: 1%‐25%) and HDL‐C (CI: 10%‐30%) levels compared with those on ETV. No change in TGL was observed in either group. Conclusions: A greater decline in TC, LDL‐C and HDL was observed in CHB carriers receiving TDF compared with ETV. These data may influence anti‐viral choice in CHB carriers at risk for CVD. Abstract : Linked Content This article is linked to Huang et al and Shaheen et al papers. To view these articles visithttps://doi.org/10.1111/apt.14266 andhttps://doi.org/10.1111/apt.14282 .